Diabetes in day case general and vascular surgery: A multicentre regional audit. Issue 4 (17th January 2020) - Fletcher, Edward; Askari, Alan; Yang, Yunfei; Adegbola, Samuel; Al‐Obudi, Yasser; Bernstein, Darryl; Patel, Krasha; Gupta, Amit; Abbasi, Omar; Anda, Hasna; Birdi, Harjot; Rabie, Mohammed; et al.
Summary: Background: People with Diabetes Mellitus (DM) are at increased risk of postoperative complications if their HbA1C readings are not well controlled. In the UK, there are clear national guidelines requiring all people with DM to have HbA1C blood testing within 6months before undergoing surgery and that these readings should be below 69 mmol/mol if this is safe to achieve. The aim of this study was to determine whether hospitals in the region were compliant with the guidelines. Methods: Data were prospectively collected from seven hospitals across the East of England region from 1st October 2017 to 31st March 2018 (6 months) in all people with DM undergoing elective day case procedures in General and Vascular surgery for benign disease. Results: A total of 181 people with DM were included in the study, of whom 77.9% were male patients and the median age was 63 years. The three most commonly performed operations were laparoscopic cholecystectomy (20.9%, n = 38/181), inguinal hernia repair (20.4%, n = 37/181) and umbilical/para‐umbilical hernia repair (11.0%, n = 20/181). In keeping with the national guidelines, only 86.7% (n = 157/181) of patients had an HbA1C tested within 6 months prior to their surgery date. Of the patients who had a preoperative HbA1C, 14 (n = 14/157, 8.9%) had an HbA1C ≥ 69 mmol/mol, and 12 (n = 12/14, 85.7%) of these proceeded to surgery without optimisation of their HbA1C. Conclusion: A significant proportion of people with diabetes undergoing elective day case procedures in our region do not have HbA1C testing within 6 months of their procedure as recommended by the national guidelines. In patients who do have a high HbA1C, the majority still undergo surgery without adequate control of their DM. Greater awareness amongst healthcare workers and robust pathways are required for this vulnerable group of patients if we are to reduce the risk of developing postoperative complication rates.